An Update on Poly(ADP-ribose) Polymerase I-A Brief Review - Negi, Preeya; Lakshmanan, Kaviarasan; Patel, Praveen K.; Rajagopal, Kalirajan; Byran, Gowramma (Mini Reviews in Medicinal Chemistry, 2023)
Poly (ADP-ribose) polymerase 1 (PARP1) plays important roles in both DNA repair and transcription, and the interplay of these processes in relation to cellular function and disease states has not been well defined. The tumor-suppressor effects of PARP inhibitors have attracted significant interest in the development of novel cancer therapies. As PARP1 binding motifs may be readily found in promoter elements of DNA repair genes, the expanding role of PARP1 in DNA repair does not have to be independent of transcription. The discovery of ADP-ribose binding modules that bind to various forms of mono- and poly-ADP-ribose has provided important insights into how ADPribosylation regulates different cellular pathways. Among the four distinct PAR-binding modules discovered so far, it is the macrodomain alone that, in addition to possessing binding activity, in some instances, also supports a catalytic activity toward ADP-ribose derivatives. However, the development of PARP inhibitors as chemopotentiating agents has been limited by an increase in observed toxicity, mainly myelosuppression, necessitating dose reduction of the cytotoxic chemotherapeutic agent and the PARP inhibitor. Hence, it presents an opportunity to rationally develop combinations of PARP inhibitors with new classes of DNA repair inhibitors that are on the horizon and classical cytotoxic agents. Clinical trials of PARP inhibitors are investigating various uses of these approaches in cancer. Recent studies on the clinical significance of PARP1 inhibitors are discussed in this review. These recent research advances will inform the selection of patient populations who can benefit from the PARP inhibitor treatment and the development of effective drug combination strategies.
Keywords: prostate cancer